An Awareness of Corporate Social Responsibility and Corporate Ethics Among UG Students - Praveen Kumar; Dr. Amit Kumar Tiwari (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Corporations have a big part in creating and growing communities. Companies participate in a variety of communities and groups to promote integrated development. Corporate social responsibility is a major ethical duty for businesses, and they are more committed to advancing the community in which they operate. Corporate social responsibility mandates that they support community infrastructure, social, and economic development, as well as the holistic growth of every member of society. This paper aims to understand the significance of the 2014 amendments to the Companies Act (Amended) with CSR and how corporate ethics have become crucial to promoting community development. Based on information gathered from respondents and an examination of secondary sources, they examine the phenomena of development and offer recommendations for community development. The article examines how 93% of the plays a significant role in advancing corporate ethics through CSR and legal aid for community development operations.